Takotsubo cardiomyopathy - review of current literature - Dominika Jarosz; Aleksandra Grudzińska; Paulina Dudzińska; Małgorzata Milanowska; Hanna Tsitko (Kazimierz Wielki University, 2022)
Takotsubo syndrome (TTS) also known as broken heart syndrome is acute cardiac disease, which is characterized by reversible ventricular motion abnormalities, in the absence of justifying coronary artery disease. The clinical entity was first described in Japan in 1991. The word "Takotsubo" is a container used by the Japanese to catch octopus, which has a narrow neck and a relatively wide base, which resembles the heart's shape in TTS. The cardiomiopathy predominantly affects postmenopausal women and is often preceded by emotional (death of close family member, domestic abuse) or physical (external injury, severe pain) stress. The exact pathophysiological mechanism has not yet been fully clarified. Inordinate amount of catecholamines released into bloodstream after stress attack plays a crucial role in the pathogenesis of TTS. Symptoms of Takotsubo cardiomyopathy such as chest pain and dyspnea are similar to acute myocardial infarction due to it TTS requires careful diagnosis. The main tools for making diagnosis are echocardiography, coronary angiography, ECG, cardiac biomarkers and cardiac magnetic resonance. The syndrome is usually reversible, nevertheless number of patients may develop complications such as cardiogenic shock, arrhythmias, heart failure. Treatment is mostly supportive including Angiotensin-converting enzyme (ACEi) inhibitors and angiotensin receptor blockers (ARBs), which may reduce the likelihood of recurrent episodes. Generally patients with TSS have favourable prognosis, although some deaths are reported. This article is a review of current medical knowledge about Takotsubo syndrome based on available publications in Pubmed and Google Scholar databases.